Responsible management understanding human nature, ethics, and sustainability - Ogunyemi, Kemi. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
This book serves as a valuable complementary text for courses on Ethics, Responsibility, Leadership, Corporate Social Responsibility, and Sustainability, which mostly tend to neglect their human nature dimensions. It provides an understanding of human nature and its uniqueness and complexity, which helps managers in today's business world to better manage and to respect self, others, and the environment. It also provides the foundation for learning ethical behavior, leadership, responsibility, sustainable management, and corporate social responsibility. Without this angle, an MBA might tend to focus primarily on financial success in different dimensions--operational quality, financial strategy, workforce motivation, cost-cutting strategies, etc. and people may forget to take cognizance of the implications of their own nature and that of the people through whom they have to work. Future leaders and shapers of sustainable organizations and societies cannot afford to have such a knowledge gap. Having these discussions helps students understand that the reason to be ethical goes beyond self-interest and profit motives to the very foundations of human nature.
Acknowledgment -- Testimonies -- 1. Introduction -- Module 1. Managing oneself -- 2. The human manager -- 3. The beginning of self-management -- 4. Abstraction and reflection -- 5. A capacity for good -- 6. Integration in complexity -- Module 2. Working with others -- 7. Diversity and uniqueness -- 8. All around the manager -- 9. People (not assets, resources, or capital) -- Module 3. Human progress -- 10. Setting personal and professional goals -- 11. Choosing the means -- 12. Scripting and re-scripting self -- 13. The manager at work -- Module 4. The full picture -- 14. Business in society -- 15. In conclusion -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (p. 135-140) and index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Social responsibility of business; Management; abstraction and reflection; anthropology; behavioral ethics; business; business and society; career success; case study; character building; commitment; communication; corporate social responsibility; development; diversity; emotion; ethics; experiential learning; freedom; fulfillment; human nature; human resource management; intellect; leadership; locus of control; management; managing people; organizational behavior; PRME; respect; responsibility; sustainability; values; virtue; will; work; workplace situations; Electronic books